Mixed-method study of the etiquette and custom cultural activity space and its construction wisdom in Bubeibu traditional Village, Yuxian County, China - Guaini Jiang; Yajun Zhang; Chunju Li; Qianyi Xu; Xuan Yu (Journal of Asian Architecture and Building Engineering)
The cultural practices encompassing etiquette and customs, along with their associated spaces, play a crucial role in preserving traditional Chinese culture. However, these cultural elements are currently under significant and irreversible threats, necessitating the strengthening of relevant theories and case studies for their safeguarding. In light of this, following field investigations conducted in 47 traditional villages in Yuxian County, we selected Bubeibu Village as our case study to analyze its etiquette and custom cultural activities, spatial characteristics, and construction wisdom. We collected first-hand information through on-site investigations and conducted a comprehensive quantitative analysis from four perspectives (the overall structure of space, point space, linear space, and areal space) on three types of cultural activity spaces (festivals, ceremonies, and operas) within Bubeibu Village. In conclusion, we summarize the spatial characteristics of etiquette and custom cultural activities and highlight their construction wisdom. Our findings serve as foundational data for establishing digital databases related to Bubeibu Village, providing support for village planning and dynamic supervision. Insights into spatial characteristics and construction wisdom can also be valuable for reinvigorating Bubeibu Village and revitalizing local culture, contributing to the preservation of rural heritage worldwide.